SPIRITUALITY AS A RESOURCE FOR COPING WITH CANCER: ANALYSIS OF THE DISCOURSE OF PATIENTS IN A FOCUS GROUP (REMUNOM, 2026)
The present study aimed to analyze how people diagnosed with cancer experience spirituality during the process of illness, identifying its meanings, functions, and implications for emotional coping and health care. This qualitative study was conducted at a cancer support institution, using a focus group with eight participants with a confirmed diagnosis of cancer. The testimonials were recorded, transcribed, and analyzed using the Collective Subject Discourse (CSD) method, allowing the identification of central ideas about the experience of spirituality in the context of illness. Three central themes emerged: 1) the emotional impact of the diagnosis, marked by fear, anguish, and uncertainty; 2) the sources of support mobilized by the participants, with emphasis on family support, social networks, and charitable institutions; and 3) spirituality as a fundamental coping resource, offering comfort, meaning, hope, and emotional strength, often linked to religiosity and religious practices. The discourses reveal that spirituality contributes to reframing the experience of suffering and sustaining the patient in the face of the possibility of finitude. The study shows that spirituality is an essential dimension in the experience of cancer and should be recognized as an integral component of health care. The findings reinforce the need to incorporate this dimension into the training and practice of health professionals (psychologists, nursing technicians, as well as nurses who are responsible for intensive care units, among others), favoring more humane, holistic care approaches that are sensitive to the biopsychospiritual needs of patients.